Bruckner Győző (1877–1962) - Stipta, István (Gerundium, 2012)
Győző Bruckner (1877–1962). Between the two world wars, the director and prominent teacher of the Augustan Evangelical Academy of Law—which was moved to Miskolc after Preşov was annexed to Czechoslovakia— was Győző Bruckner, who came from a German-Saxon Zipser family. His primary fields of professional interest were the cultural history of the Uplands region, the history and legal relations of the Spiş mining towns. hese interests of his remained enduring and he published a number of fundamental studies and monographs pertaining to these subjects. Bruckner is, however, known not only for his work in legal and cultural history, but he also played a signiicant role in the life of the evangelical church, and he had a crucial role in the development of the legal academy of Miskolc. In addition, he published a series of books and a periodical in support of the work of the college he headed. He lived to see the closing-down of his beloved legal academy, of which, after he retired in pension, he himself wrote a history